Assessment of water quality indices for selected Malaysian river / Chee Chun Khoon - Chee, Chun Khoon (2018)
Water quality is very crucial in ensuring the sustainability of human activities and survival. In Malaysia, river water quality is constantly monitored and evaluated by the water quality index (WQI) established by Department of Environment (DOE). Water quality index (WQI) is a quantitative indicator that can easily determine the pollution condition of river water. It utilises six critical water quality parameters to portray the river water quality. Weightage is assigned to each parameter to signify the influence of the parameter. The WQI is then quantified to obtain a numerical value, which represents the pollution level of the river water. The pollution status of the river water can also be categorised in various classes, depending on the intended use of the water body. Besides, the water quality index is also compared with other standards used in several countries. The advantages and disadvantages of each standards are determined. A new graphical method, “Eco-Heart Indicator” is proposed to serve as an alternative tool to portray the health of the river water. In this research, Selangor River is selected as the basis of study. The data obtained from Department of Environment (DOE) are used to plot Eco-Heart Indicator and compared with the Water Quality Index (WQI). The graphical representation of the water quality is hoped to become an easier communication tool to the public in addressing the awareness of river water status.